(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
In the context of globalization and the digitalization of the economy, the role of artificial intelligence (AI) in accelerating the digital transformation of national economies has become increasingly relevant. This article is dedicated to analyzing the impact of AI on the development of Uzbekistan’s digital economy within the framework of the strategic program "Digital Uzbekistan 2030". The potential of AI as a tool for enhancing the efficiency of public administration, stimulating economic growth, improving the quality of life for the population, and ensuring the sustainable development of the country is examined. The study’s findings underscore the importance of developing and implementing a comprehensive approach to AI integration, which will enable Uzbekistan to achieve its digitalization goals and ensure sustainable development in the long term.